PaaS cloud platform based on container technology - Lei QI; Haifeng ZHANG; Tianxiao ZHANG; Hao ZHU; Xu CHEN (Dianxin kexue)
With the development of internet service and IaaS cloud,the PaaS cloud was discussed in the construction and application of IT support systems.How to take into technological evolution and how to build PaaS architecture,were analyzed.How to implement a system of centralized management,supervision,sharing and scheduling was introduced.How to achieve unity of application deployment and how to achieve high availability for data center were discussed.